Pengaruh Model Pembelajaran Predict Observe Explain dan Motivasi terhadap Higher Order Thinking Skills Siswa Pada Mata Pelajaran Biologi SMPN 9 Merangin : (The Influence of Predict Observe Explaining Learning Models and Motivation Toward Students 'High Order Thinking Skills in Biology Lessons in Biology Subjects at SMPN 9 Merangin) - Nurfadilah Nurfadilah; Revis Asra; Syaiful Syaiful (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to determine the effect of using the Predict Observe Explain learning model, and motivation on students' HOTS in the biology subject matter of the human respiratory system. This research is a quantitative research. The design used in this study is a quasi-experimental design. There are two types of instruments used as a means of collecting data (learning motivation questionnaire and learning test). The instrument used has been validated first by the validator. The results showed that the results of the control class with the pretest average were 68.90, the posttest was 72.65, while the pretest experimental class was 71.40, while the posttest was 79.45. posttest scores can be interpreted as follows: HOTS ability of students who use conventional learning models and have low motivation with an average score (mean) = 70.00. HOTS ability of students who use conventional learning models and have high motivation with an average score (mean) = 74.08. The HOTS ability group of students who use the Poe learning model and have low motivation with an average score (mean) = 72.29. While the HOTS Ability Group of students who use the Poe learning model and have high motivation with an average score (mean) = 83.31. Key words: Predic observe explain, Motivation, Higher order thinking skill Abstrak Penelitian ini bertujuan untuk Mengetahui pengaruh penggunaan model pembelajaran Predict Observe Explain, dan motivasi terhadap HOTS siswa pada mata pelajaran biologi materi sistem pernapasan manusia. Penelitian ini merupakan penelitian kuantitatif. Desain yang digunakan dalam penelitian ini adalah eksperimen semu (Quasi Experimental Design). Instrumen yang digunakan sebagai alat pengumpulan data ini ada dua jenis (angket motivasi belajar dan tes belajar). Instrumen yang digunakan terlebih dahulu telah divalidasi oleh validator. Hasil penelitian menunjukkan bahwa hasil kelas control dengan rata-rata pretest yakni 68,90,posttest yakni 72,65, sedangkan kelas eksperimen pretest yakni 71,40, sedangkan posttest yakni 79,45. nilai postest dapat dintrepretasikan sebagai berikut: Kemampuan HOTS siswa yang menggunakan model pembelajaran konvensional dan memiliki Motivasi rendah dengan perolehan nilai rata-rata (mean) = 70.00. Kemampuan HOTS siswa yang menggunakan model pembelajaran konvensional dan memiliki Motivasi tinggi dengan perolehan nilai rata-rata (mean) = 74.08. Kelompok Kemampuan HOTS siswa yang menggunakan model pembelajaran Poe dan memiliki Motivasi rendah dengan perolehan nilai rata-rata (mean) = 72.29. Sedangkan Kelompok Kemampuan HOTS siswa yang menggunakan model pembelajaran poe dan memiliki Motivasi tinggi dengan perolehan nilai rata-rata (mean) = 83.31. Kata kunci: Predic observe explain, Motivasi, Higher order thinking skill